Incidence and determinants of the surgical site infection:a hospital based longitudinal study - Sutariya, Pinakin K.; Chavada, Mallika V. (International Surgery Journal, 2016)
Background: Surgical site infection (SSI) is one of the common nosocomial infections and associated with increased length of hospital stay, hospital cost, patient morbidity and mortality. Methods: A prospective longitudinal study was conducted at a tertiary care centre of Ahmadabad city. Total 480 patients operated for general surgical procedures between the periods of January 2016 to June 2016 were included for the present study. Data were collected from the data sheet which included basic demographic detail of the patient, diagnostic criteria and associated risk factors. Data entry and analysis was done in software Epi info version 7.0. Chi square was used to identify association of the risk factor with outcome. P-value <0.05 was considered to be statistically significant. Results: In present study, 9.4% of the patients had SSI. The risk factors associated with SSI were age (18.3% versus 7.1%), diabetes (25.5% versus 7.6%), type of anaesthesia (general = 13.6% versus regional=7.1%), type of surgery (emergency = 21.7% versus elective = 7.3%), duration of surgery (17.9% versus 7.2%), type of wound (dirty = 28.4% versus clean = 2.99%), pre-operative hospital stay (27.3% versus 3.3%) and presence of drain (15.2% versus 7.2%). Conclusions: Our study emphasizes that age, type of surgery and wound, preoperative hospital stay, co-morbidity and drain have definite correlation with SSI. A standard infection surveillance protocol needs to be practiced stringently in an attempt to reduce the SSI rate.